Clinical Features and Outcomes of Gallbladder Polyps in Children - Ferzeliyev, Orxan; Oğuz, Berna; Soyer, Tutku; Boybey Türer, Özlem; Haliloglu, Mithat; Tanyel, Feridun Cahit (Turkish Journal of Gastroenterology, 2022)
Background: Gallbladder polyps are rare lesions protruding into the gallbladder lumen with variable clinical presentation. No standard treatment algorithm has been developed for pediatric gallbladders, and the malignant potential of the gallbladder is not clear in children. Therefore, a retrospective study was performed to evaluate the clinical features and treatment options of gallbladder polyps in children. Methods: Between 2014 and 2020, children diagnosed with gallbladder polyps were evaluated for age, gender, clinical features, results of follow-up with ultrasound findings, and treatment options retrospectively. Results: The records of 15 patients with a mean age of 13.2 years (2-20 years) were included. The male: female ratio was 7 : 8. Gallbladder polyps was detected incidentally in 73.3% (n = 11) of the patients. Four (20%) of the patients were symptomatic (26.7%) and complained about abdominal pain. Laboratory tests were normal except in 3 patients who showed slightly increased liver function tests. Two of the patients had 3 polyps on admission. The polyps were 2-10 mm in size. The size of the polyp increased in 5 patients (33.3%) and disappeared in 4 patients (26.6%) in follow-up ultrasound examinations. Five of the patients underwent cholecystectomy and 1 of them was scheduled for surgery. Five of the asymptomatic patients who have polyps less than 10 mm in size are still on follow-up. In patients with cholecystectomy, the histopathology of gallbladders revealed cholesterol polyps (n = 2) and hyperplastic polyps (n = 2). One of the patients with cholecystectomy showed no polyps in histopathological evaluation. Conclusion: Despite the lack of a standardized algorithm, our data suggested that multiple polyps, polyps with increased in size or greater than 10 mm, and the presence of symptoms might require cholecystectomy in children. Asymptomatic patients with small-sized polyps can be identified using ultrasound, and the polyps may disappear during the subsequent follow-up. Cite this article as: Ferzeliyev O, Oğuz B, Soyer T, Boybey Türer Ö, Haliloglu M, Tanyel FC. Clinical features and outcomes of gallbladder polyps in children. Turk J Gastroenterol. 2022;33(9):803-807.